Ursula K. Le Guin e Kim Stanley Robinson: Diálogos Utópicos - Fernandes, Fábio (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
ABSTRACT: The article explores the similarities and differences in Ursula K. Le Guin’s and Kim Stanley Robinson’s narrative discourses, highlighting their distinct but complementary approaches to utopian literature. Le Guin uses the reduction of the world to explore social and political critiques, mainly in The Dispossessed, while Robinson adopts logistical utopia, focusing on practical and sustainable solutions to environmental and social problems, exemplified in New York 2140 and the Mars Trilogy. The analysis addresses how both authors use dialogues and metalogues to engage readers in in-depth discussions about the construction of alternative futures, highlighting the relevance of their works in the contemporary context.